The Influence of Experience, Fear, Awareness of Cyber Attacks on the Acceptance of Banking Technology Moderated by Perceived Benefits in the Development of Digital-Based Banking Services in Indonesia - Ilham Zharfan Satrya (Green Publisher Indonesia, 2025)
This study analyzes the influence of experience, fear, and awareness of cyberattacks on the acceptance of banking technology in Indonesia, moderated by perceived benefits. Utilizing a quantitative approach, data were collected through questionnaires distributed to users of digital banking services. The analysis results indicate that both experience and fear of cyberattacks do not significantly affect the acceptance of banking technology, with p-values of 0.414 and 0.199, respectively. In contrast, awareness of cyberattacks has a significant positive effect on the acceptance of banking technology, with a p-value of 0.039. However, perceived benefits did not successfully moderate the relationship between experience and fear of cyberattacks and the acceptance of banking technology, with all p-values exceeding 0.05. These findings suggest that public understanding of cyberattacks can enhance trust and acceptance of banking technology, despite the inherent risks. This research provides important insights for the development of digital banking services in Indonesia, emphasizing the need for education on cybersecurity to improve technology acceptance.An abstract must accompany each manuscript; This abstract must be completely consistent on its own (eg, without numbers, tables, equations or reference citation), not exceeding 250 words and written as a paragraph. The abstract should include research objectives, methodology, and findings.